ChemInform Abstract: Tetrapalladium‐Containing Polyoxotungstate [PdII4 (α‐P2W15O56)2] 16—: A Comparative Study. Issue 2 (January 2015) - Izarova, Natalya V.; Maksimovskaya, Raisa I.; Willbold, Sabine; Koegerler, Paul
Abstract Na16 [Pd4 (α‐P2W15O56)2] ·71H2O is synthesized from a mixture of Na12[α‐P2W15O56] dissolved in 0.5 M AcONa buffer (pH 4.2) and solid Pd(NO3)2 (25 °C, 1 h, 55% yield).